PARTICULATE ORGANIC MATTER AS A SOIL QUALITY INDICATOR OF SUGARCANE PLANTATIONS IN EAST JAVA - Nurhidayati Nurhidayati; Endang Arisoesialaningsih; Didik Suprayogo; Kurniatun Hairiah (AGRIVITA, Journal of Agricultural Science, 2012)
This study is aimed to test the hypothesis that the soil quality of sugarcane plantations closely linked to the particulate organic matter (POM) and earthworm’s populations. The research was conducted at five sites in Malang, East Java. The sites were selected based on differences in average annual rainfall and two types of soil management : with and without organic input. Soil samples taken from a depth of 0-20 cm were analyzed total organic C (TOC), total N, POM-C, and POM-N and earthworm’s population density and biomass. The TOC were corrected by the clay  content using pedotransfer equations so obtained TOCref. The interaction between differences in annual rainfall and two types of the treatments significantly (p